Digital libraries and multimedia archives : 12th Italian Research Conference on Digital Libraries, IRCDL 2016, Florence, Italy, February 4-5, 2016, Revised selected papers /: 12th Italian Research Conference on Digital Libraries, IRCDL 2016, Florence, Italy, February 4-5, 2016, Revised selected papers. (2017) - Unknown
No abstract available